NORMATIVE STUDY OF LAW ENFORCEMENT OF CAPITAL MARKET CRIMES IN THE INDONESIAN LEGAL SYSTEM - JAMALUDIN; TATA ELIESTIANA DYAH A (Yayasan Pendidikan Aksara Cendikia, 2025)
This research aims to identify the qualifications of capital market criminal acts and analyze their legal enforcement within the framework of the Indonesian legal system. The type of research used in this research is normative legal research using statutory and conceptual approaches. The research results show that: 1) The qualification of criminal acts in the Capital Markets Law includes three main forms, namely criminal acts of fraud, market manipulation and insider trading. These three types of criminal acts have special characteristics because they focus on the misuse of strategic information, not on material objects, so the process of proof requires in-depth precision because the formulation of the offense is still abstract and not fully in line with the development of capital market crime modes which are increasingly complex and technology-based. 2) Law enforcement in the Indonesian capital markets sector still faces various obstacles, both from authority and technical aspects. Even though OJK has Polri and PPNS investigators, the effectiveness of investigations is still limited due to dependence on the KUHAP mechanism, inadequate technical capabilities of investigators, and sub-optimal inter-agency coordination. This condition makes case handling less responsive, so it is necessary to strengthen regulations and institutional capacity